Diseño de una máquina cizalladora y dobladora de láminas metálicas para prácticas de laboratorio (2019)
The present project is elaborated with the purpose of designing a machine capable of measure the necessary pressure, in your hydraulic system, to bend and cut sheets metallic materials in order that from this data the students in the laboratory of processes calculate the force required for these processes. In the first stage of the project, an overview of the cutting machines by shearing and bending of metal sheets. In turn, describe the two main types of machines for shearing metal sheets which are the alligator type machine and the guillotine type. The two are also exposed methods for folding a sheet; by punch in V and by edge method. Finally, a comparison of the functional characteristics of the machine versus machines in the industry.